Pengembangan Perilaku Sosial Anak Dan Sikap Kooperatif Melalui Permainan Tradisional Tam Tam Buku - Mevira Indri; Sri Milfayetty; Retna Astuti (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2022)
Development of Children's Social Behavior Through Traditional Games, Books and Cooperative Attitudes. Postgraduate Program in Psychology, University of Medan Area. This study aims to determine the development of children's social behavior through traditional games of Tam Tam Buku and cooperative attitudes in TK. Mother. This type of research is Action Research. The research was carried out in 2 cycles, the first cycle was carried out in two actions, because it had not reached 80%, the research was continued in the second cycle with two actions. The subjects of the research were the 18 children of Group B in Bunda Kindergarten. The object of this research is social behavior. Social Behavior research instruments include Cooperating, Playing with peers, Competing, Respecting friends, Being able to share with friends, Helping friends, Friendly children, Children are not selfish, Children imitate, Sympathize, Children smile and laugh. The method of data collection is done through observation. The data analysis technique used descriptive qualitative and quantitative. The results of this study indicate that the hypothesis can be accepted, namely that the traditional game of Tam Tam Buku and cooperative attitudes can develop social behavior. This can be proven from the results of the observation before the action that the percentage of children who developed very well, for social behavior was 5.56% and in the second cycle it increased to 85.35%.